Trade, investment and the environment - Ward, Halina (Royal Institute of International Affairs LondonGB, 2000)
Focuses on the ongoing debate on the relationship between trade, investment and the environment. Seeks to explore some of the main ideas and positions in the rapidly evolving debate on how to secure 'win-win' solutions. Focuses on how to resolve some of the more technical issues as they relate to the rulles of the multilateral trading system. Looks st the relationship between investment and sustainable development in two lights: the issues relating to foreign direct investment itself and lessons from the Multilateral Agreement on Investment.